Exploration of the solar system by infrared remote sensing - Hanel, R. A. (Cambridge University Press, 2003)
This book describes all aspects of the theory, instrumental techniques and observational results of the remote sensing of objects in our Solar System through studies of infrared radiation. Fully revised since publication of the first edition in 1992, it now incorporates the latest technologies, new mission results and scientific discoveries. It also includes a fully up-dated bibliography to reflect the advances made in this field during the past ten years. All planets from Mercury to Pluto, many of their satellites, asteroids and comets are discussed. The presentation will appeal to advanced students and professional planetary science researchers, although some chapters are of wider interest. The authors have drawn on their extensive experience at the NASA-Goddard Space Flight Center to produce a definitive account of what can be learned from infrared studies of our planetary system.